Public investment and economic activity in Mexico, 1925-1981 - Felipe Fonseca; Manuel Gómez-Zaldívar; Daniel Ventosa-Santaulària (Kiel Institute for the World Economy (IfW), 2019)
Mexican economic historiography recognizes the key role that public investment played in the country's economic performance from the post-revolutionary period until the beginning of the economic liberalization that began in the mid-1980s. However, there is no concrete empirical evidence that this was the case. In this study, the authors construct a historical database of public investment - both total and broken down into its main components - for the period from 1925 to 1981, in order to measure the impact it had on economic activity. Given the possible presence of crowding-out effects between public investment and private investment, in their analysis the authors control for the latter. The results suggest that public investment had a significant impact on output one which varies depending on the category of public investment considered.
Keywords: N16; H54; C32; 330; economic activity; federal public investment; cointegration